Side Effects Comparison of Coronavirus Vaccines Among Healthcare Workers in Shoushtar, Iran - Edris Nabizadeh; Fatemeh Honarmandpour; Rezvan Mashhadizade; Azam Honarmandpour (SAGE Publishing, 2023)
Objective: Vaccination is one of the effective ways to fight against COVID-19 disease. Various vaccines have been designed during the coronavirus pandemic. Each of the used vaccines has beneficial effects as well as side effects. Healthcare workers were among the first vaccinated persons against COVID-19 in different countries. The current study aims to compare the side effects of AstraZeneca, Sinopharm, Bharat, and Sputnik V on healthcare workers in Iran. Methods: This descriptive study was conducted from July 2021 to January 2022 on 1639 healthcare workers who received the COVID-19 vaccines. Data were collected using a checklist that contained questions related to systemic, local, and severe side effects of the vaccine. The collected data were analyzed using the Kruskal-Wallis, Chi-square, and trend chi-square. P  < .05 was regarded as a significant statistical difference. Results: The most commonly injected vaccines were Sinopharm (41.80%), Sputnik V (36.65%), AstraZeneca (17.75%), and Bharat (3.80%), respectively. At least 37.5% of participants reported one complication. The most common side effects after 72 hours of the first and second doses were as follows: injection site pain, fatigue, fever, myalgia, headache, and chill. Overall complication rates were reported as follows: AstraZeneca (91.4%), Sputnik V (65.9%), Sinopharm (56.8%), and Bharat (98.4%). Bharat showed the highest overall side effects, while Sinopharm had the lowest overall side effects. Also, our results indicated that individuals with a previous history of positive COVID-19 infection had a higher rate of overall complications. Conclusions: The majority of participants did not show life-threatening side effects after the injection of 1 of the 4 studied vaccines. Since it was well accepted and tolerable by the participants, it can be used widely and safely against SARS-CoV-2.